The Development of an Illustrated Storybook about the Rain Cycle Using Digital Painting to Enhance Students' Learning Interest - Ramdhan, Syaipul; Maisaroh, Siti; Saeful, Ahmad (JURNAL SISFOTEK GLOBAL, 2025)
While a wide variety of learning media exists today, each with its own strengths, this abundance can also be overwhelming for students, making it difficult to choose materials that are both effective and easy to understand. Currently, the learning media at SDN Curug 1 are often considered monotonous, relying heavily on text and featuring illustrations that do not adequately support the educational process. This research aims to transform the learning experience from tedious to engaging by developing an illustrated storybook about the rain cycle using digital painting techniques. The methodology employed includes observation, interviews, and a literature review, informed by expert sources and the specific conditions at SDN Curug 1. The primary outcome of this study is an illustrated storybook about the rain cycle. This book serves as a new educational tool for students at SDN Curug 1, designed to deepen their understanding of the subject matter and spark their interest in learning.